Implementasi Peningkatan Kerja Sama Tim, Work Life Balance, Trasformational Leadership Terhadap Kinerja Karyawan: Studi pada Karyawan PT. Pegadaian Cabang Sukabumi - Ria Mulvianti; Dicky Jhoansyah; Resa Nurmala (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the era of globalization, the role of human resources for companies is becoming increasingly important, human resources determine the survival of the company. Human resources aim to develop the company. Pegadaian is a State-Owned Enterprise (BUMN) which has the status of a People's Credit institution with a Community Savings system to be able to meet needs to be effective. The aim of this research is to determine the implementation of teamwork, work life balance, transformational leadership on employee performance at PT. Sukabumi branch pawn shop. The method used in this research is a quantitative method with a descriptive approach. The sample in this study was 33 samples who were employees of PT. Pegadaian Sukabumi Branch using saturated sampling technique. Data was obtained through a research questionnaire distributed to all samples containing 20 statements regarding the variables of teamwork, work life balance, transformational leadership and employee performance, using an Ordinal measurement system. The data obtained was carried out various tests such as validity tests and reliability tests, classic assumption tests and then analyzed using SPSS 26 software testing. The results of the research showed that there was a significant influence between the variables of teamwork and work life balance on employee performance, but there were negative results for the variables. Transformational leadership on employee performance.